KAJIAN KRIMINOLOGI TERHADAP MODUS KORUPSI DALAM KASUS ASABRI - Muhammad Luthfi; Ika Dewi Sartika Saimima (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
Corruption, as an extraordinary crime, has a destructive impact on the state and erodes public trust. The PT ASABRI scandal highlights the vulnerability of public fund management and the complexity of its modus operandi. This study aims to examine specific policies (preventive and repressive) based on ASABRI's corruption modus operandi to prevent similar cases in the future and identify obstacles to resolving cases from a criminological perspective. The research method used is Sociology-Criminology with a library research approach. The discussion indicates that preventive policies should focus on strengthening governance and internal oversight, increasing transparency (real-time reporting, whistleblowing), and improving investment regulations (limiting risky investments, strict due diligence, prohibiting conflicts of interest). Meanwhile, repressive policies require multidisciplinary and coordinated law enforcement and the application of proportionate sanctions that provide a deterrent effect (maximum penalties, revocation of rights, corporate liability, and optimization of asset recovery). Obstacles to resolving the ASABRI case include the complexity of the modus operandi (organized networks, sophisticated money laundering, elite involvement), challenges in the legal process (limited resources, lengthy bureaucracy, difficulty in proving evidence, weak coordination), and socio-political factors (low public trust, media influence, resistance to reform, and the phenomenon of moral holiday).